Poligamy in Morocco and pension in Spain. The Spanish Supreme Court and the public policy exception - Valverde Martínez, María José; Carrascosa González, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
This paper deals with the criteria used by the Supreme Court of Spain in order to answer the question of whether two women, widows of the same husband, both legally married in Morocco, can be regarded as beneficiaries of the widow’s pension generated by their husband. The Supreme Court of Spain implements a mitigated public policy effect even though no international convention applies to the case. Once guaranteed that the legal foundations of Spanish society are safe, the Spanish Supreme Court activates an attenuated public policy to allow some legal effects of a marriage legally celebrated in Morocco. Among them, the court admits that both wives can be considered beneficiaries, in equal parts, of the Spanish widow’s pension.